2018
DOI: 10.1177/2047487318763958
|View full text |Cite
|
Sign up to set email alerts
|

A reference equation for maximal aerobic power for treadmill and cycle ergometer exercise testing: Analysis from the FRIEND registry

Abstract: Background Maximal oxygen uptake (VOmax) is a powerful predictor of health outcomes. Valid and portable reference values are integral to interpreting measured VOmax; however, available reference standards lack validation and are specific to exercise mode. This study was undertaken to develop and validate a single equation for normal standards for VOmax for the treadmill or cycle ergometer in men and women. Methods Healthy individuals ( N = 10,881; 67.8% men, 20-85 years) who performed a maximal cardiopulmonary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
0
10

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(73 citation statements)
references
References 32 publications
1
62
0
10
Order By: Relevance
“…With the publication of several databases with a large population with the direct measurement of VO 2 max, a great interest was developed in the development of equations to estimate VO 2 max. Recently, the FRIEND equation predicted the VO 2 max with an overall error >4 times lower than the error associated with the traditional American College of Sports Medicine equations (5.1±18.3% vs. 21.4±24.9%, respectively) [18,19]. Souza and Silva developed a bicycle and treadmill equation derived from the FRIEND data and compared this equation with those that previously existed, and they found that the VO 2 max values derived using the former equation were significantly closer to the actual VO 2 max values than that calculated using the older equations.…”
Section: Discussionmentioning
confidence: 99%
“…With the publication of several databases with a large population with the direct measurement of VO 2 max, a great interest was developed in the development of equations to estimate VO 2 max. Recently, the FRIEND equation predicted the VO 2 max with an overall error >4 times lower than the error associated with the traditional American College of Sports Medicine equations (5.1±18.3% vs. 21.4±24.9%, respectively) [18,19]. Souza and Silva developed a bicycle and treadmill equation derived from the FRIEND data and compared this equation with those that previously existed, and they found that the VO 2 max values derived using the former equation were significantly closer to the actual VO 2 max values than that calculated using the older equations.…”
Section: Discussionmentioning
confidence: 99%
“…Peak V O 2 was defined as a 30-s rolling average of the six highest 5-s oxygen uptake values. Participants were classified as having impaired peak VO 2 if they achieved < 85% of predicted values for children/ adolescents [16] or adults [17] in line with American Thoracic Society guidelines for CPET interpretation [18]. The anaerobic threshold was calculated using the V-slope method [19], with the VO 2 at the anaerobic threshold expressed as an absolute value and as a proportion of each participant's predicted peak VO 2 .…”
Section: Exercise Capacitymentioning
confidence: 99%
“…6 Numerous limitations associated with the W/H equations have been reported, including the fact that they were derived from a relatively small and homogeneous cohort. 7,8…”
Section: How Do We Evaluate Oxygen Uptake and Should It Be Normalized For Age?mentioning
confidence: 99%